Chinese herbal medicine Shufeng Jiedu capsule for mild to moderate COVID-19: a multicenter, randomized, double-blind, placebo-controlled phase II trial - Lu, Chun-li; Yang, Liu-qing; Jin, Xin-yan; Friedemann, Thomas; Li, Yu-fei; Liu, Xue-han; Chen, Xiao-ying; Zou, Xiang-yun; Zhang, Bing-rui; Wang, Fu-xiang; Lin, Yuan-long; Tang, Yi-min; et al. (Frontiers in Pharmacology, 2024)
The COVID-19 pandemic has had a profound global impact, although the majority of recently infected cases have presented with mild to moderate symptoms. Previous clinical studies have demonstrated that Shufeng Jiedu (SFJD) capsule, a Chinese herbal patent medicine, effectively alleviates symptoms associated with the common cold, H1N1 influenza, and COVID-19. This study aimed to assess the efficacy and safety of SFJD capsule in managing symptoms with mild to moderate COVID-19 infection.Methods: A randomized, double-blind, placebo-controlled trial was conducted from May to December 2022 at two hospitals in China. Mild and moderate COVID-19-infected patients presenting respiratory symptoms within three days from onset were randomly assigned to either the SFJD or placebo groups in a 1:1 ratio. Individuals received three times per day SFJD capsules or placebo for five consecutive days. Participants were followed up for more 14 days after their RT-PCR nucleoid acid test for SARS-CoV-2 turned negative. The primary outcome measure was time to alleviate COVID-19 symptoms from baseline until the end of follow-up.Results: A total of 478 participants were screened, ultimately, 407 completed the trial after randomization (SFJD, n=203; placebo, n=204). No statistically significant difference in baseline parameters were observed between the two groups. Median time to alleviate all symptoms was seven days in the SFJD group compared with eight days in the placebo group (P=0.037). Notably, SFJD group significantly attenuated fever/chills (P=0.04) and headache (P=0.016) when compared with the placebo group. Furthermore, median time taken to reach normal body temperature within 24 hours was reduced by seven hours in the SFJD group compared to the placebo group (P=0.033). No deaths or instances of serious or critical conditions occurred during this trial period; moreover no serious adverse events were reported.The trial was conducted in a unique controlled hospital setting, and the 5-day treatment with SFJD capsules resulted in a one-day reduction in overall symptoms, particularly for headache and fever/chills among COVID-19-infected participants with mild or moderate symptoms. Compared to placebo, SFJD capsules were found to be safe with fewer side effects. SFJD capsules could potentially serve as an effective treatment for alleviating mild to moderate symptoms of COVID-19.